ANTENA MIMO-UWB 4X4 DUAL BANDS NOTCHED DENGAN MENGGUNAKAN METODE EBG DAN SLITS - Jamil, Wahdina; Nursal, Firdaus; yulindon, Yulindon (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2023)
In this paper, a Multiple-Input-Multiple-Output (MIMO) antenna that can work in Ultra-Wideband (UWB) technology is presented. The antenna can work in frequencies of 3.1-10.6 GHz, has dual bands notched, and in small dimensions at once. The antenna is made in size 34 x 34 x 1.6 mm using a 4-element planar monopole antenna with L-shape and C-shape slits on the radiator. This antenna research was designed and simulated using CST Studio Suite 2019. The design results were fabricated for testing through a Vector Network Analyzer and Anechoic Chamber. The ground plane on the rhombic slot-shaped antenna by utilizing the slot on the antenna radiator produces notched bands from simulations at 3.39-3.64 GHz (WiMAX) and 4.57-5.82 GHz (WLAN). The fabricated antenna has a bandwidth impedance value through S11